Plants with antioxidant activity and their potential use as sun protector agents in Costa Rica - Arguedas Herrera, Raquel (2023)
Aims: To carry out a bibliographic review related to plants available in Costa Rica that have demonstrated antioxidant power and a sun protection factor (SPF) suitable to be used in sunscreen products. Methods: The bibliographic review was carried out using different descriptors and by consulting different databases. Results: Information about antioxidant power about acerola, avocado, carrots, passion fruit, moringa, banana, pumpkin and amaranth, guava, matico, ginkgo, blackberry, mango, coffee was obtained. The information obtained suggests that the mentioned plants could be used for the formulation of sunscreens. Conclusion: Sun protection products should be used every day to prevent skin damage; some sunscreens produce allergic reactions, so it is necessary to investigate natural options to be used in sun protection products. Some natural products exhibit SPF values that allow their incorporation as sun protection agents, adjuvants, or enhancers in sunscreens.